The IUCN Red List and newspaper coverage of threatened freshwater eel species in Japan: A variable but limited influence - Kenzo Kaifu; Hiromi Shiraishi; Atsushi Ishii; Aoi Sugimoto (PLoS ONE, 2025)
The IUCN Red List is a vital tool for identifying threatened species and raising public awareness. This study examined how the listing of freshwater eels ( Anguilla spp.) influenced newspaper coverage in Japan, a major consumer of eels. We analysed 8387 eel-related articles from four major newspapers between 1992 and 2021 using text-mining and statistical methods, along with manual review of a part of the articles. Peaks in article numbers coincided with major events, such as the IUCN listing of the Japanese eel as Endangered in 2014. However, the influence of the Red List was short-lived and limited in strength, with minimal media attention given to non-native eel species such as European eel. Category-specific analysis revealed that issues related to food and trade dominated media coverage, while conservation-focused reporting was less prominent. Our findings suggest that while the Red List can momentarily increase media attention, its impact on long-term public awareness is limited. Strengthening expert engagement, international cooperation, and consumer education could be essential to enhance the conservation impact of the Red List.